ISLAMIC EDUCATION CURRICULUM DEVELOPMENT MODEL 2013 CURRICULUM VERSION - Nisa'atun Nafisah (STKIP PGRI Situbondo, 2023)
Position Islamic Religious Education Curriculum (PAI) as the center in the whole process of education, as direction for all activity education to achieve the purpose. Because of that to reach something successful curriculum it is necessary a nice system that loads components of the best curriculum and is supported by the structure of the best curriculum. The Aim of PAI curriculum is to Upgrade productive, creative, innovative, and effective operating faith and piety, for Upgrade what ever studied participants educate about religion as well as life practice every day. The method used in the study is with method search references or studies literature. Research results show that component curriculum at least must consist of four components that are purpose, content, process, and assessment. because the discussion previously about PAI learning then special for PAI curriculum in it must load values Islamic teachings on each component of the course must each other related. The criticism writer needs he added mark religious and collaborative for maximizing the PAI curriculum in implement inside the school.